Embrace the suck : what I learned at the box about hard work, (very) sore muscles, and burpees before sunrise - Madden, Stephen, active 2011 (HarperWave, an imprint of HarperCollinsPublishers, 2014)
A lifelong amateur athlete and former editor of "Bicycling" magazine chronicles the year he devoted to trying to master all of the basic CrossFit exercises and immersing himself in the paleo diet.